2019
DOI: 10.1039/c9ra01573f
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric and vibrational properties of Be2C, BeMgC and Mg2C using first-principles method

Abstract: The EFF of Mg2C. A very good thermoelectric has the EFF above the horizontal lines marked at 300 and 800 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The list of 131 materials used in this work corresponds to some of the most studied and useful insulators and semiconductors for thermal management and thermoelectrics [39][40][41][42][43][44]. From the first-principles calculations it can be observed that most of them fulfill the condition > γκ, where γ = 1 nm mK W −1 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The list of 131 materials used in this work corresponds to some of the most studied and useful insulators and semiconductors for thermal management and thermoelectrics [39][40][41][42][43][44]. From the first-principles calculations it can be observed that most of them fulfill the condition > γκ, where γ = 1 nm mK W −1 (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The list of 131 materials used in this work corresponds to some of the most studied and useful insulators and seminconductors for thermal management and thermoelectrics [33][34][35][36][37][38]. From the first-principles calculations it can be observed that most of them fulfil the condition ℓ > γκ, where γ = 1 nm•mK/W (Table I).…”
Section: Resultsmentioning
confidence: 99%